Analysis of fetal intestinal enzymes in amniotic fluid for the prenatal diagnosis of cystic fibrosis - Mulivor, Richard A. (1987)
Amniotic-fluid intestinal alkaline phosphatase activity, gamma-glutamyltranspeptidase activity, and leucine-aminopeptidase activity were quantitated to assess their reliability for the prenatal diagnosis of cystic fibrosis. The results indicate that for each of these enzymes an arbitrary cutoff point could be chosen that would enable one to correctly predict the outcome for the majority of at-risk pregnancies. However, some false positives and false negatives occurred with each enzyme. To obtain optimal diagnostic discrimination, the three enzyme values obtained for each sample were combined into a single linear discriminant function that proved to be a more accurate indicator of the outcome of the pregnancy. This was especially important for those cases in which the predicted outcome as based on the individual enzyme results was in disagreement. From the cases studied here, it appears that this method can be expected to give a correct prediction in ∼96.5% of all 25%-at-risk pregnancies. False positives can be expected in ∼1.4% of the pregnancies and false negatives in ∼2.2%.